2008
DOI: 10.1590/s0004-27492008000600025
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic ophthalmia - histopathological correlation with fluorescein and indocyanine green angiography: case report

Abstract: This study correlates fluorescein angiography (FA) and indocyanine green angiography (ICGA) to histopathologic findings in a patient with sympathetic ophtalmia. A male with a perforated trauma in right eye presented after two months a decrease in visual acuity of the left eye. FA and ICGA were performed and the images were correlated with the histopathologic findings of the enucleated eye; FA showed background areas of homogeneous hypofluorescence in the arterial and venous phases, as well as areas of granular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…ICGA is a crucial adjunct to FFA in the diagnosis of these entities, as the choroid is primarily involved in both pathologies. In acute SO, ICGA shows multiple hypocyanescent spots corresponding to choroidal infiltration with inflammatory cells and Dalen-Fuchs nodules on histopathological examination [ 8 , 9 ]. However, ICGA findings in chronic SO have not been frequently described in the literature, with inconsistent findings in rare case reports, such as one by Bernasconi et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICGA is a crucial adjunct to FFA in the diagnosis of these entities, as the choroid is primarily involved in both pathologies. In acute SO, ICGA shows multiple hypocyanescent spots corresponding to choroidal infiltration with inflammatory cells and Dalen-Fuchs nodules on histopathological examination [ 8 , 9 ]. However, ICGA findings in chronic SO have not been frequently described in the literature, with inconsistent findings in rare case reports, such as one by Bernasconi et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, if the hypocyanescent spots faded in the late phase, then these spots likely indicated active choroiditis [57]. However, Casella et al reported that even when the hypocyanescent spots persisted through the late phases, comparison with histopathologic findings and FA revealed that these spots corresponded to Dalen-Fuchs nodules and not chorioretinal atrophy [58] as posited by Bernasconi and colleagues [57]. Of interest, these hypocyanescent spots were observed to resolve after treatment and paralleled clinical improvement [58].…”
Section: Diagnosismentioning
confidence: 93%
“…However, Casella et al reported that even when the hypocyanescent spots persisted through the late phases, comparison with histopathologic findings and FA revealed that these spots corresponded to Dalen-Fuchs nodules and not chorioretinal atrophy [58] as posited by Bernasconi and colleagues [57]. Of interest, these hypocyanescent spots were observed to resolve after treatment and paralleled clinical improvement [58]. Moshfeghi et al showed that although the posttreatment early and intermediate phases of ICGA appeared normal, the hypocyanescent spots reappeared in the late phases [59].…”
Section: Diagnosismentioning
confidence: 99%
“…These spots occur due to the presence of cellular infiltration of the choroid, DF nodules, or overlying edema. Casella et al 100 showed that these hypocyanescent spots persist throughout the phases of ICGA. These hypocyanescent spots are noted to lessen or vanish once the treatment with corticosteroid is started and are consistent with clinical improvement.…”
Section: Icga (Indocyanine Green Angiography)mentioning
confidence: 98%